Sex hormones and competitive bidding - Burkhard C. Schipper (University of California, Department of Economics, 2014)
We correlate competitive bidding and profits in symmetric independent private value first-price auctions with salivary testosterone, estradiol, progesterone, and cortisol in more than 200 subjects. Bids are significantly positively correlated and profits are significantly negatively correlated with basal salivary progesterone but only for females who do not use hormonal contraceptives. Surprisingly, we have null findings for basal testosterone, estradiol, and cortisol for both males and females. We show that our finding for progesterone is not mediated by risk aversion or bidding mistakes. No hormone responds to total profits in the auctions except for a small positive response of the stress hormone cortisol in males.
Keywords: C72; C91; C92; D44; D81; D87; 330; auctions; gender; competition; aggression; risk-taking; endocrinological economics